Progressive Intracranial Vertebral Artery Dissection Presenting with Isolated Trigeminal Neuralgia-Like Facial Pain - Tomoki Nakamizo; Takashi Koide; Hiromichi Miyazaki (Case Reports in Neurological Medicine)
Intracranial vertebral artery dissection (IVAD) is a potentially life-threatening disease, which usually presents with ischemic stroke or subarachnoid hemorrhage. IVAD presenting with isolated facial pain is rare, and no case with isolated trigeminal neuralgia- (TN-) like facial pain has been reported. Here, we report the case of a 57-year-old male with IVAD who presented with acute isolated TN-like facial pain that extended from his left cheek to his left forehead and auricle. He felt a brief stabbing pain when his face was touched in the territory of the first and second divisions of the left trigeminal nerve. There were no other neurological signs. Magnetic resonance imaging (MRI) of the brain 7 days after onset revealed dissection of the left intracranial vertebral artery without brain infarction. The pain gradually disappeared in approximately 6 weeks, and the patient remained asymptomatic thereafter, except for a brief episode of vertigo. Follow-up MRI revealed progressive narrowing of the artery without brain infarction. This case indicates that IVAD can present with isolated facial pain that mimics TN. IVAD should be considered in the differential diagnosis of acute facial pain or TN.